2018
DOI: 10.4467/20838476si.18.002.10407
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Signal Settings Optimization Using Gradient Descent

Abstract: We investigate performance of a gradient descent optimization (GR) applied to the traffic signal setting problem and compare it to genetic algorithms. We used neural networks as metamodels evaluating quality of signal settings and discovered that both optimization methods produce similar results, e.g., in both cases the accuracy of neural networks close to local optima depends on an activation function (e.g., TANH activation makes optimization process converge to different minima than ReLU activation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The authors in [15] presented a comparative analysis of optimization algorithms in optimizing phase lengths of fixed traffic signal controllers. Authors in [16] and [17] have proposed a solution to tackle the problem of congestion at an intersection by applying a decision tree classification algorithm, whereas, [18] have used gradient descent optimization technique.…”
Section: Literaturementioning
confidence: 99%
“…The authors in [15] presented a comparative analysis of optimization algorithms in optimizing phase lengths of fixed traffic signal controllers. Authors in [16] and [17] have proposed a solution to tackle the problem of congestion at an intersection by applying a decision tree classification algorithm, whereas, [18] have used gradient descent optimization technique.…”
Section: Literaturementioning
confidence: 99%
“…Usually, the quality of settings can be evaluated using traffic simulations [2], but in the case of large road networks and evaluating traffic for long time periods, this method can be too time-demanding [3]. One of the recent and interesting approaches to solve this issue is to use surrogate models based on machine learning (e.g., neural networks or LightGBM) to approximate the outcomes of traffic simulations [4,5,6,7]. Such methods can be very efficient, as they return the results of evaluations a few orders of magnitude faster than in the case of computer simulations while preserving a good accuracy of approximations [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the recent and interesting approaches to solve this issue is to use surrogate models based on machine learning (e.g., neural networks or LightGBM) to approximate the outcomes of traffic simulations [4,5,6,7]. Such methods can be very efficient, as they return the results of evaluations a few orders of magnitude faster than in the case of computer simulations while preserving a good accuracy of approximations [4,5,6,7]. For example, the recent works showed that it may be possible to approximate the outcomes of traffic simulations where the input is a vector representing signal settings and the output computed by the simulations is the total time of waiting on red signals in a given urban area and in a given time period [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations